Collective Knowledge and Cultural Practices in the Marriage Ceremony of the Chamling Rai Community - Rai, Dewa Kumar; Rai, Laxmi Kumar; Rai, Kalpana (DMC Journal, 2025)
This paper explores the collective knowledge and practices in the marriage ceremony of the Chamling Rai community. Modernization, migration, and socio-economic changes are affecting indigenous cultures and practices, although the Chamling Rai community continues to sustain the marriage ceremony as a collective practice. In the research, open-ended interviews and secondary data are the main research methods for data collection. Sanchep practices in the marriage of the Chamling Rai community is the main finding of the research. Although ritual dialogues, decision-making, voluntary collective labor, shared meal, collective blessing, and group dances are also main collective indigenous knowledge and practices in the marriage ceremony. These collective functions and practices help the mechanisms to transfer indigenous knowledge, social norms, and values across generations. The study shows that the marriage ceremony of the Chamling Rai community plays a vital role in preserving cultural collective practices.